Job classification for completed investment projects in Dhi Qar Governorate - Abdul Latif, Makki Ghazi; Khalaf, Anwar Kazem (Al-Adab Journal, 2022)
The topic of the research has addressed the completed investment projects in Dhi Qar Governorate at the level of sectors (residential, commercial, industrial, health, educational, recreational, agricultural, and service), and what these projects provide a positive role in improving the economy of the province and what is reflected on the living and social situation on residents of the governorate, Data related to these projects has been obtained from the field study and from the investment authority in the study area, which has been an attempt to know the geographical distribution in the administrative units of the governorate, as well as knowledge of the spatial differences that occurred. The factors that contributed to this difference Data / study showed that there is variation in the concentration of investment projects and their concentration in the centers of districts and specifically in the center of the province (spend Nasiriyah).